Communicating Educational Research to Policymakers and the Public: Strategies for Increasing Impact and Uptake - Aruku, Kalita Joseph; Utsu, Ushie Charles; Obi, Anthony Nku; Edim, Roselyn Edim (International Journal of Humanities, Education, and Social Sciences, 2025)
Educational research plays a critical role in identifying effective pedagogical approaches, understanding learning challenges, and informing policy decisions aimed at improving educational outcomes, yet a persistent gap remains between the production of research findings and their uptake by key stakeholders. This study investigates the challenges and effective strategies for communicating educational research findings to policymakers, educators, parents, and the general public in Nigeria. Employing a qualitative methodology based on the analysis of 80 online documents (reports, articles, policy papers, and websites), the research examines key communication barriers, successful strategies, researcher–stakeholder engagement mechanisms, and evaluation methods. The findings underscore the need for tailored communication approaches that emphasize visual aids, storytelling, and participatory methods to enhance understanding and uptake of research evidence in policy and practice. The study recommends establishing dedicated communication channels, fostering collaborations between researchers and stakeholders, and implementing robust evaluation frameworks to ensure the effectiveness and impact of educational research dissemination efforts.